The exercise of religious freedom in educational institutions in the light of ecthr jurisprudence - Valutytė, Regina; Gailiūtė, Dovilė (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
The implementation of the freedom of religion or belief in educational environment, in particular the use of religious symbols and obligatory religious education, has been, and continues to be, a matter of controversy and discussion in a number of countries. A number of cases brought before the ECtHR concerning the application of Article 9 of the Convention and Article 2 of Protocol 1 of the ECHR show that parties to the ECHR still face difficulties in guaranteeing religious freedom in the educational environment consistently with the requirements of the ECHR, the analysis of which is the core of the Article. The majority of European states seek to avoid indoctrination in state education and teaching by offering exemption mechanisms or lessons in substitute subjects, or by giving pupils the choice of whether or not to sign up to a religious studies class. However, as it is clear from the jurisprudence of the ECtHR, the exemption or choice itself does not guarantee that in practice the Member States ensure an education consistent with religious convictions in line with the requirements set forth explicitly and implicitly in Article 2 of Protocol No. 1 and Article 9 of the ECHR. Furthermore, in the majority of cases regarding the display of religious symbols, the ECtHR justified the interference as ‘necessary in a democratic society’ in pursuance of the legitimate aim of protecting the rights and freedoms of others and of public order. However, the Court’s findings in the cases concerning Islamic symbols, on the one hand, and Christian religious symbols, on the other hand, raise a discussion about ‘double standards’ applicable to the different religions.
Keywords: wolność religijna; orzecznictwo Europejskiego Trybunału Praw Człowieka